Relationship between structure and inhibition behaviour of quinolinium salts for mild steel corrosion: Experimental and theoretical approach - Mourya P.; Singh P.; Tewari A.K.; Rastogi R.B.; Singh M.M. (My University, 2025)
Corrosion inhibition behaviour of quinolinium salts on mild steel (MS) corrosion in 0.5M H2SO4 was investigated at various concentrations and temperatures by gravimetric and electrochemical techniques. The polarization curves indicated that these salts function as mixed inhibitors. Relevant kinetic and thermodynamic parameters like CR, Ea, δHa0, δSa0, Kads and δGads0 were determined and discussed. The adsorption of salts on MS leading to inhibition was found to follow the Langmuir adsorption isotherm. The existence of a protective film on MS was confirmed by SEM and AFM techniques. XPS and quantum chemical calculations were carried out to establish the mechanism of corrosion inhibition. © 2015 Elsevier Ltd.